Comparing the Nonlinear Dynamic Acoustic Parameters of Healthy Adult and Pediatric Voices. (December 2018) - Chou, Adriana; Schrof, Colin; Polce, Evan; Braden, Maia; McMurray, James; Jiang, Jack
Objectives: The aims of this study were to compare nondysphonic adult and pediatric voices using linear and nonlinear acoustic parameters and to evaluate the ability of adult spectrum convergence ratio (SCR) and rate of divergence (ROD) reference values to correctly identify a pediatric voice type as periodic or aperiodic. Methods: Twenty adult and 36 pediatric nondysphonic voice samples were collected and analyzed using linear and nonlinear acoustic parameters. Absence of voice disorder was confirmed using perceptual acoustic and spectral analysis. Mean values for jitter, shimmer, SCR, and ROD were compared between adults and children, across specific age groups, and within genders. Using adult reference values for SCR and ROD, samples were classified as primarily periodic or aperiodic and typed using spectral analysis. Rates of accurate typing were also compared between subject groups. Results: Overall, jitter and shimmer were similar among the adult and pediatric age groups. ROD was significantly different among the 3 pediatric and 1 adult group; the pediatric age groups were similar to one another. Adult SCR was also significantly different from all of the pediatric age groups. In adult men, ROD and SCR were significantly different from all of the pediatric age groups; the pediatric age groups were similar to one another. In female subjects, ROD was significantly different among all age groups. The ROD and SCR reference values were significantly better at categorizing adult voice types compared with pediatric voice types. Conclusions: In healthy subjects, SCR and ROD have discriminatory power for identifying adult versus pediatric voices, while jitter and shimmer cannot differentiate between the 2 groups. However, age- and gender-specific pediatric reference values must be determined to accurately classify voice types using SCR and ROD.